Bernoulli -- Find the general solution 1. The problem statement, all variables and given/known data Find the general solution of: y'+xy=xy^3 2. Relevant equations Bernoulli's Equation 3. The attempt at a solution y'+xy=xy^3 (y^-3)y'+x(y^-2)=x Let v=(y^-2), thus v'=((-2y^-3)y' Then, -v'/2+xv=x Multiply through by (-2) v'-2xv=-2x Now it's in first-order linear so I multiply by e^int(-2x)dx = e^(-x^2) (e^(-x^2))v'-2xe^(-x^2)=2xe^(-x^2) This is where I'm getting stuck :( BECAUSE: the integral of e^(-x^2) is the "error function?" According to Wolfram, integral e^(-x^2) dx = 1/2 sqrt(pi) erf(x)+constant ---- Anyone get anything different or know where I might have messed up? THANK YOU!!